2016
DOI: 10.1007/s13277-015-4350-x
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA AK027294 involves in the process of proliferation, migration, and apoptosis of colorectal cancer cells

Abstract: This study is aimed to investigate the differentially expressed long non-coding RNAs (lncRNAs) in colorectal cancer and its potential biological function. Colorectal adenoma is the precancerous lesions of colorectal cancer, so in this study, we used colorectal adenoma as negative control. The global lncRNA expression profile in colorectal cancer and adenoma was evaluated by bioinformatics. The biological functions and potential mechanism of AK027294 were investigated in HCT116, HCT8, and SW480 colorectal cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…LncRNAs play important roles in various types of cancer and exert multiple functions in cancer cell proliferation, apoptosis, migration, and invasion. [13][14][15] LncRNA HNF1A-AS1 is a novel identied singleexon gene with 2455 nucleotides and localized at the chromosome 12q24.31.…”
Section: -10mentioning
confidence: 99%
“…LncRNAs play important roles in various types of cancer and exert multiple functions in cancer cell proliferation, apoptosis, migration, and invasion. [13][14][15] LncRNA HNF1A-AS1 is a novel identied singleexon gene with 2455 nucleotides and localized at the chromosome 12q24.31.…”
Section: -10mentioning
confidence: 99%
“…In a study conducted in gastric cancer, Cai et al demonstrated that FRLnc1 overexpression could promote cancer cell migration and metastasis and identified TGF-β1 and Twist as the downstream effectors of FRLnc1 [132]. In CRC, Niu et al revealed that AK027294 downregulation significantly inhibited CRC cell migration and promoted cell apoptosis by regulating Twist, caspase-3, caspase-8, Bcl-2, MMP12, MMP9 expression [133]. In gallbladder cancer, LincRNA-ROR and AFAP1-AS1 are also reported to regulate Twist expression to promote EMT process [134,135].…”
Section: Twist and Lncrnasmentioning
confidence: 99%
“…Previous studies have indicated that H19 exhibits dysregulated expression in GC (13,14), hepatocellular carcinoma (15), bladder cancer (16), breast cancer (17) and esophageal cancer (18), and that itmay cause tumor promoting and suppressing effects (19). Niu et al (20) screened lncRNA expression profilesfrom colorectal cancer and adenoma samples, and identified a novel lncRNA, AK027294, which was associated with cell proliferation, migration and apoptosis in colorectal cancer cells. Li et al (21) and Song et al (22) investigated the lncRNA expression patterns in GC with a microarray, and identified 135 differentially expressed lncRNAs in GC tissues compared with non-tumor adjacent tissues (NATs).…”
Section: Introductionmentioning
confidence: 99%